Tracing membrane biofouling to the microbial community structure and its metabolic products: An investigation on the three-stage MBR combined with worm reactor process. (April 2019) - Liu, Jia; Liang, Xiongwei; Yang, Chunxue; Yu, Shaopeng; Guo, Hong
Highlights: Flavobacteria, Firmicutes and Chloroflexi caused slow membrane fouling of the S-MBR. The enrichment of β-proteobacterium brought about the rise-associated in TMP of the C-MBR. SMPc in conjunction with EPSc and SMPp accelerated the membrane fouling. A quick rise in SMPc triggered an abrupt increase in TMP. The EPSc and SMPp caused the sustained increase in TMP. Abstract: The biofouling characteristics of an MBR (S-MBR) combined with the worm reactor and a conventional MBR (C-MBR) were analyzed, respectively, over the three-stage (fast-slow-fast) process. Whether it was in the C-MBR or the S-MBR, the species of the active sludge (AS) were similar to that of the cake sludge (CS) in stage 1 (before day 1), the bacterial adsorption and the metabolites attachment contributed to this transmembrane pressure (TMP) rise. In the stage 2, the TMP increasing rate of the C-MBR was eight times more than that of the S-MBR. During this period, a characteristic community colonized the AS and CS of the S-MBR with the microbes, ie Flavobacteria, Firmicutes and Chloroflexi which were responsible for the degradation of extracellular polymeric substances (EPS) and soluble microbial products (SMP). These dominant species caused the slower accumulation of biofouling metabolites in the CS, resulting in the slow rise-related in TMP. Meanwhile, the enrichment of β-proteobacterium and the absence of Mycobacterium and Propionibacterium in AS and CS of the C-MBR were deemed as the main biological factors bringing about the rise-associated in TMP. In the stage 3, the biofilm was matured, and the cake layer was more compacted, which resulted in an abrupt rise in TMP and severe membrane fouling. Additionally, the statistical analysis revealed that a highly correlation between the TMP increasing rate and the content of carbonhydrates in SMP (SMPc ). When the SMPc content increased slowly, there was a relatively slow biofouling. But, when the SMPc increasing rate was greater, it led to a more serious membrane fouling with the sudden TMP jump. Additionally, there was also a highly significant correlation coefficient for the TMP rise and the content of carbonhydrates in EPS (EPSc ) and the protein in SMP (SMPp ), rather than the protein in EPS (EPSp ). The cluster analysis showed that the microbes contributing to membrane fouling were more abundant in the C-MBR, while the microbes related to organic compounds degradation were more abundant in the S-MBR. There was significant correlation between the microbes and their metabolites. The SMPc in conjunction with EPSc and SMPp were the main factors accelerating the membrane fouling. It was concluded that a quick rise in SMPc triggered an abrupt increase in TMP, while the EPSc and SMPp caused the sustained increase in TMP.